The hidden minority? Dilemmas around the status of the russophone Ukrainians in contemporary Ukraine - Karolina Koziura (Sprawy Narodowościowe. Seria nowa, 2014)
The hidden minority? Dilemmas around the status of the russophone Ukrainians in contemporary Ukraine